Analisis Kestabilan Model Susceptible Infected Isolation Hospitalized Recovered (SIIsHR) pada Penyebaran COVID-19 - Putri, Aliffia Dewi; Bahri, Susila; Baqi, Ahmad Iqbal (Prodi Pendidikan matematika Universitas Islam Majapahit (UNIM), Mojokerto, Indonesia, 2023)
This study aims to find out how big the transmission rate of COVID-19 is. The SIHR (Susceptible, Infected, Isolation, Hospitalized, Recovered) model was applied. This model has two equilibrium points, namely a disease free equilibrium point and a disease-endemic equilibrium point. The stability at the two equilibrium points is asymptotically stable. In this study, the model was simulated using COVID-19 data for DKI-Jakarta Province from 1 January 2021 to 1 January 2022. Numerical simulations with various values of the rate of treatment and self-isolation parameters were carried out to see the effect of these two parameters on reducing the spread